Perceptions of the benefits of the basic medical insurance system among the insured: a mixed methods research of a northern city in China - Wang, Peng; Li, Shuyi; Wang, Zhizhen; Jiao, Mingli; Zhang, Yuchao; Huang, Weiqi; Ning, Ning; Gao, Lijun; Shan, Linghan; Li, Ye; Wu, Qunhong (Frontiers in Public Health, 2023)
Background The perceptions of the benefits of the basic medical insurance system among the insured not only reflect the system’s performance but also the public’s basic medical insurance policy literacy, valuable information for countries that have entered the stage of deepening reform. This study aims to examine the factors that affect the perceptions of the benefits of the basic medical insurance system in China, diagnose the key problems, and propose corresponding measures for improvement. Methods A mixed method design was used. Data for the quantitative study were obtained from a cross-sectional questionnaire survey (n = 1045) of residents of Harbin who had enrolled for basic medical insurance system. A quota sampling method was further adopted. A multivariate logistic regression model was then employed to identify the factors influencing the perceptions of the benefits of the basic medical insurance system, followed by semi-structured interviews with 30 conveniently selected key informants. Interpretative phenomenological analysis was used to analyze the interview data. Results Approximately 44% of insured persons reported low perceptions of benefits. The logistic regression model showed that low perceptions of the benefits of the basic medical insurance system was positively correlated with the experience of daily drug purchases (OR=1.967), perceptions of recognition with basic medical insurance system (OR=1.948), perceptions of the financial burden of participation costs (OR=1.887), perceptions of the convenience of using basic medical insurance for medical treatment (OR=1.770), perceptions of the financial burden of daily drug purchases costs (OR=1.721), perceptions of the financial burden of hospitalization costs (OR=1.570), and type of basic medical insurance system (OR=1.456). The results of the qualitative analysis showed that the key problem areas of perceptions of the benefits of the basic medical insurance system were: (Ⅰ) system design of basic medical insurance; (Ⅱ) intuitive cognition of the insured; (Ⅲ) rational cognition of the insured; and (Ⅳ) the system environment. Conclusions Improving the perceptions of the benefits of the basic medical insurance system of the insured requires joint efforts in improving system design and implementation, exploring effective publicity methods of basic medical insurance system information, supporting public policy literacy, and promoting the health system environment.